Epilepsy research in Africa: A scoping review by the ILAE Pediatric Commission Research Advocacy Task Force. Issue 9 (21st June 2022) - Samia, Pauline; Hassell, Jane; Hudson, Jessica; Ahmed, Azim; Shah, Jasmit; Hammond, Charles; Kija, Edward; Auvin, Stéphane; Wilmshurst, Jo
Abstract: Objective: Despite the high prevalence of epilepsy in Africa, evaluation of epilepsy research trends on the continent is lacking. Without establishing effective research, improvement in care for people with epilepsy cannot be effectively strategized or targeted. Methods: A scoping review of the peer‐reviewed literature on epilepsy from Africa (1989–2019) was conducted. The aim was to understand from this what areas are well researched versus underresearched based on published epilepsy topics. Results: A total of 1227 publications were identified and assessed. A significant increase in publications occurred over the 30 years assessed. African author leadership was evident in most reports. Nine countries had >50 publications identified; the remaining 45 countries had <50 or no publications. Research studies were typically of lower quality (case series and observational studies). Research themes were more focused on clinical epilepsy (descriptive observational studies) and social aspects (qualitative surveys). However, there were a number of unique and strong themes, specifically for neurocysticercosis and nodding syndrome, where strong research collaborations were evident, basic science understandings were explored, and interventional models were established. Significance: Despite Africa being the continent with the most countries, it is lacking in the quantity, quality, and for some areas, relevance of research on epilepsy. Targeted approaches are needed to upskill the strength of research undertaken with more basic science, interventional, and randomized controlled studies. Themes of research need to promote those with unique African content but also to align with current international research areas that have impact on care delivery, such as epilepsy surgery and epilepsy genetics. For this to be possible, it is important to strengthen research hubs with collaborations that empower Africa to own its epilepsy research journey.